2015
DOI: 10.3174/ajnr.a4554
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the Sparse Temporal Acquisition Technique in Resting-State Brain Network Analysis

Abstract: BACKGROUND AND PURPOSE:The ability of sparse temporal acquisition to minimize the effect of scanner background noise is of utmost importance in auditory fMRI; however, it has considerably lower temporal efficiency and resolution than the conventional continuous acquisition method. The purpose of this study was to determine whether sparse sampling could be applied to resting-state research by comparing its results with those obtained by using continuous acquisition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Therefore, we cannot completely rule out that differences in insular connectivity patterns might have been biased by auditory processes in musicians and nonmusicians. However, this is unlikely as recent studies have not found between‐group differences in auditory network activation during resting state [Palomar‐García et al, ] nor when comparing standard continuous acquisition with sparse acquisition [Yakunina et al, ]. Another consideration concerns global signal removal.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we cannot completely rule out that differences in insular connectivity patterns might have been biased by auditory processes in musicians and nonmusicians. However, this is unlikely as recent studies have not found between‐group differences in auditory network activation during resting state [Palomar‐García et al, ] nor when comparing standard continuous acquisition with sparse acquisition [Yakunina et al, ]. Another consideration concerns global signal removal.…”
Section: Discussionmentioning
confidence: 99%
“…ICA is well suited even for sparse sampling data, as long as the samples are evenly spaced with regard to the TR (which was the case in our study). Moreover, ICA based on sparse sampling and continuously acquired data yielded highly consistent networks in a previous study [Yakunina et al, ]. Importantly, while univariate data analysis approaches are biased to detect effects in non‐lesioned regions (due to reduced statistical power in regions lesion overlap; [Meinzer et al, ; Price et al, ]), ICA offers a number of options to overcome this bias.…”
Section: Methodsmentioning
confidence: 99%
“…Mean overall gray matter signal was not included as a confound as doing so shifted the whole brain connectivity distribution towards predominantly negative values. The data were detrended and a 0.01 to 0.1 Hz bandpass filter applied to remove low-frequency drifts and physiological high-frequency noise, consistent with previous research using connectivity analysis of sparse acquisition fMRI data (Yakunina et al, 2015). …”
Section: Methodsmentioning
confidence: 99%